Ibda' binafsi - Che Mohd Salleh, Marhanum (Kulliyyah of Economics and Management Sciences International Islamic University Malaysia, 2021)
This short writing is written to remind myself and all readers that if we want to ensure that we and our family will be united in the paradise, we should start with ourselves. Surah At-Thur (52) verse 21 have clearly mentioned ―And those who believed and whose descendants followed them in faith - We will join with them their descendants, and We will not deprive them of anything of their deeds. Every person, for what he earned, is retained.‖. Therefore, we should increase our iman and „amal in order to bring our family members with us in the Paradise.